2020
DOI: 10.1007/s11033-020-05746-3
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin improves endothelial dysfunction and aortic fibrosis in insulin-resistant SHR rats by estrogen receptors

Abstract: The aim of the work was to investigate the effects of acacetin on endothelial dysfunction and aortic fibrosis in insulin-resistant SHR rats and explore its mechanism. Seven-week-old male spontaneously hypertensive rats (SHR) were selected to establish a rat model of hypertension with insulin resistance induced by 10% fructose. The nuclear factor kappa B p65 (NF-κB p65) and Collagen I were observed by Immunohistochemistry. Immunofluorescence was used to observe estrogen receptor-alpha (ERα), estrogen receptor-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
1
21
1
Order By: Relevance
“…In recent years, anti-fibrotic mechanisms of ADSCs have been progressively elucidated [18,19]. TGF-β is one of the most classical and important signaling pathway in fibrosis pathogenesis, and its up-regulation activates hepatic stellate cells (HSCs), α-smooth muscle actin (α-SMA) expression, and the synthesis of ECM proteins, such as collagens [20]. Moreover, the TGF-β signaling pathway mediates the anti-fibrotic effects of ADSCs in diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, anti-fibrotic mechanisms of ADSCs have been progressively elucidated [18,19]. TGF-β is one of the most classical and important signaling pathway in fibrosis pathogenesis, and its up-regulation activates hepatic stellate cells (HSCs), α-smooth muscle actin (α-SMA) expression, and the synthesis of ECM proteins, such as collagens [20]. Moreover, the TGF-β signaling pathway mediates the anti-fibrotic effects of ADSCs in diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount clinical and epidemiological evidence have indicated that hypertension is one of the major risk factors for cardiovascular disease, characterized by impaired vascular structure and endothelial function, which is the early vascular lesion of hypertension. [25] In this study, both SBP and DBP in the hypertension group were significantly higher than in the healthy group (Table 2). It has been explained in the previous studies that the increase of h1 and h3/h1 was associated with arterial stiffness.…”
Section: Discussionmentioning
confidence: 45%
“…To acquire a statistical analysis, we used SPSS 25.0 program to analyze the data. Two Independent Student T test and Mann-Whitney U test were applied for two group comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of clinical and epidemiological evidence indicates that hypertension is a major risk factor for cardiovascular disease and that it can be characterized by impaired vascular structure and endothelial function as indicators of early vascular lesions [ 27 ]. In this study, both SBP and DBP were significantly higher in the hypertensive group than in the healthy group ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%